Creating a Corpus of Multilingual Parent-Child Speech Remotely: Lessons Learned in a Large-Scale Onscreen Picturebook Sharing Task - Woon, Fei Ting; Yogarrajah, Eshwaaree C.; Fong, Seraphina; Salleh, Nur Sakinah Mohd; Sundaray, Shamala; Styles, Suzy J. (Frontiers in Psychology, 2021)
With lockdowns and the implementations of social distancing measures in place, research teams looking to collect naturalistic parent-child speech interactions have to look for methods alternative to in-lab recordings and observational studies with long-stretch recordings. We designed a novel micro-longitudinal study, the Talk Together Study, which allowed us to create a rich corpus of parent-child speech interactions in a fully online environment (N participants = 142, N recordings = 414). In this paper, we discuss the novel methods we used, and the lessons learned during adapting and running the study. These lessons learned cover nine domains of research design, monitoring and feedback: Recruitment strategies; Surveys and Questionnaires; Video-call scheduling; Speech elicitation tools; Videocall protocols; Participant remuneration strategies; Project monitoring; Participant retention; and Data quality, and may be used as recommendations for teams who are planning to conduct remote studies in the future.